Pengaruh Kompetensi Guru Terhadap Prestasi Siswa Pada SMK Pariwisata YAPPMI Jatibarang Indramayu - Agus Yudianto; Meddy Nurpratama (Risenologi, 2021)
The world of education today is growing rapidly and the problem of education is increasingly complex which continues to struggle for challenges that are left unchecked just like that, but it requires constructive thinking in order to achieve good quality. The problem in question is the teacher's teaching competence. The problem of education and teaching is a fairly complex problem where many factors influence it. One of these factors is the teacher. The teacher is a teaching component that plays an important and major role, because the teaching and learning process is very much determined by the teacher factor. The task of the teacher is to deliver the subject matter to students through communication interactions in the teaching and learning process, where the success of the teacher in delivering the material is very dependent on the smoothness of communication interactions that have an effect on the message given by the teacher The problem of education and teaching is a fairly complex problem where many factors influence it. One of these factors is the teacher. The teacher is a teaching component that plays an important and major role, because the teaching and learning process is very much determined by the teacher factor. The task of the teacher is to deliver the subject matter to students through communication interactions in the teaching and learning process, where the success of the teacher in delivering the material is very dependent on the smoothness of communication interactions that have an effect on the message given by the teacher. The competency of teachers at the YAPPMI Jatibarang Indramayu Tourism Vocational School is in very good condition. The results of the recapitulation of the respondent's score on the competence of teachers at the YAPPMI Jatibarang Indramayu Vocational School of Tourism are 993, the data is in a strongly agreed area (945 - 1125 = strongly agree), Regression Analysis. The results of data collection will be collected for each variable as a value for each respondent and can be calculated through the SPSS program. The method of analyzing data uses statistical calculations and uses the SPSS version 23 program to test the predetermined hypothesis whether it can be accepted or rejected. In this calculation the statistical calculations use a simple regression analysis model: Y = a bX + e. The achievement of students and employees at SMK Pariwisata YAPPMI Jatibarang Indramayu is in very good condition. The results of the recapitulation of scores of respondents' answers regarding student achievement at SMK Pariwisata YAPPMI Jatibarang Indramayu are 653 the data is in very good areas (630 - 750 = strongly agree). The results of statistical tests on the teacher competency variable on student achievement indicate that the R Square value is 0.220, or 22%, which means that there is an effect of teacher competence on student achievement and the remaining 78% is a variable outside the study. The value of the teacher competency t (X) is greater than the t table (2.790> 2.064) or the significance level of the t count is smaller than the alpha value (0.010 <0.05), thus that there is acceptance of H0 or acceptance of Ha which means it shows the influence of the teacher competency variable ( X) positively and significantly towards the student achievement variable (Y).